(untitled) (Itinerarios Educativos, 2022)
The introduction of technologies brought about transformations that made educators promote and produce changes in teaching and learning models for the various knowledge production scenarios. It becomes necessary to go further in the development of competences and skills to integrate them into the training of professional nurses by reorienting, modifying, and implementing innovative teaching methodologies. A didactic, real, and caring–focused integration of knowledge is needed to face cognitive, practical, and technological demands in work and social environments. The present research was conducted in the framework of a Final Project for the specialization degree in University Teaching. It proposes an integrative and didactic approach to teaching and learning practices for training students attending the program for the Bachelor’s Degree in Professional Nursing. It seeks to improve the quality of professional practices in health services without overlooking the discipline’s conceptions of to know, to know how, and to know how to be.